Effectiveness of Cognitive – Behavioral Management of Stress on Students’ Homesickness - Shahmohammadi, Nayereh (Mediterranean Journal of Social Sciences, 2011)
The present study aims to determine the effectiveness of Cognitive- Behavioral Stress Management on homesicknessamong university students.The study was conducted in a pre-test post-test experimental design. Two weeks after their arrival atthe University dormitories, 225 freshman students completed the 33-item measure of homesickness, HomesicknessQuestionnaire (Archer et al, 1998). According to this questionnaire, 88 of the students were found to be suffering fromhomesickness (their scores were 1 SD beyond the average). From this population, 50 students were randomly selected andassigned to the intervention and control group. Subjects in the experimental group, undergone 10 sessions of cognitivebehavioralstress management Training. Subjects in the control group received no treatment.Data were analyzed usingindependent t test. There were no significant differences between the two groups in the pre-test result. However, aftercompleting the stress management training, the experimental group showed significantly lower scores than the control group.Furthermore, two factors of homesickness (i.e. dissatisfaction with the university and strong attachment to home) which did notshow any differences between the groups in the pre-test results, revealed significant reduction in the post-test results of theexperimental group.The results of the present study show that cognitive-behavioral stress management training can be effectivein alleviating homesickness and the problems that the students may encounter when they enter a new university environment.